Hypereosinophilic Syndrome Secondary to Ulcerative Colitis and Primary Sclerosing Cholangitis - Davi Viana Ramos; Diogo Delgado Dotta; Luísa Leite Barros (Case Reports in Gastroenterology, 2023)
Hypereosinophilic syndrome (HES) is a rare condition characterized by hypereosinophilia in peripheral blood or tissue infiltrate and organ damage. HES has been associated with several diseases, including inflammatory bowel diseases (IBDs), especially ulcerative colitis (UC). In this report, we describe a case of a UC and primary sclerosing cholangitis patient who was diagnosed with HES and severe cardiovascular and neurological injury. During hospitalization, an extensive diagnostic workup was performed and secondary causes of hypereosinophilia were ruled out. The patient was treated with glucocorticoids and full anticoagulation with significant clinical improvement and a marked reduction in the eosinophil count. In the literature, hypereosinophilia in the IBD population has been related to the severity of the disease and worse prognosis. The high index of clinical suspicion and the accurate diagnosis of HES are essential to avoid delay in therapy and prevent complications.